Network of Asian economies. - Kok, Jun Liang. (2011)
In this project, we perform a minimum spanning tree analysis of 24 Asian countries stock index time series, with the aim to understand the causal dynamics between Asian countries. From the temporal distribution of clustered segments, we found that developing economies generally have higher volatility phase switches compared to advanced economies. We also discovered that the Asian Financial Crisis affected the involved countries in one phase, while the Subprime Crisis has two phases. The time taken for the countries to fall into crisis took two months ten days and three months six days respectively. Using the pairwise cross-correlation between countries, we constructed the minimum spanning tree (MST) for each corresponding segment for different macroeconomic phases. We discovered two distinct topologically structures in the MST, chain-like and star-like, corresponding to crisis and growth phases. Two distinct clusters, East and West Asian cluster, were also observed. In the segment-by-segment analysis of the Asian Financial Crisis, the Subprime Crisis and the Lehman Brothers Collapse that followed, similar chain-like and star-like MST structures were observed in crisis and growth phases respectively. Furthermore, we observed the MST structure transited from chain-like to star-like when the macroeconomic phase switch from crisis phase to growth phase and vice versa. From the MSTs rearrangements, we found that information processing efficiency has increased over the years as the rearrangements became simpler. We also discovered that Asia was heading towards a recovery in mid-2008 before Lehman Brothers Collapse plunged Asia into crisis again. A star-like structure observed at the end of 2009 suggested that Asia is on the road to recovery from Lehman Brothers Collapse.